2018
DOI: 10.3389/fphar.2018.01126
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effects of Rosemary Extracts Associate With Anti-inflammatory Effect and Rebalance of Gut Microbiota

Abstract: It is currently believed that inflammation acts as a central part in the pathophysiology of depression. Rosemary extracts (RE), the crucial active constituents extracted from Rosmarinus officinalis Linn, have drawn wide concerns because of their potential for anti-inflammatory effects. However, no study has highlighted the antidepressant effects of RE on chronic restraint stress (CRS) mice, and the inflammatory mechanisms related to gut microbiome have not yet been elucidated. This study showed that depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…However, none of these studies demonstrated association of carnosic acid with the anti‐depressant‐like action. Although, in chronic restraint stress model of mice, it was observed that the extract was composed of ~60% of carnosic acid (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies demonstrated association of carnosic acid with the anti‐depressant‐like action. Although, in chronic restraint stress model of mice, it was observed that the extract was composed of ~60% of carnosic acid (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The rosemary extracts were found to decrease the proportion of both Bacteroidetes and Proteobacteria while promoting an abundance of Lactobacillus and Firmicutes. With respect to the pro-inflammatory mediators, the extract reduced IL-1β, TNF-α, and p-NF-κB, indicating a protective effect for rosemary extract in mice and its implication in the antidepressant-like properties of the plant [313]. A lipid extract (D-004) of Roystonea regia increased mouse immobility in both the FST and TST but showed no effects in other behavioral tests [314].…”
Section: Dosementioning
confidence: 94%
“…3S, Supplementary Information), which produce biphasic modulation of GABA A receptors [312], have also been proposed as active constituents. In one interesting study, Guo et al [313] investigated the antidepressant effects of rosemary extracts on chronic restraint stress mice along with the inflammatory mechanisms related to the gut microbiome. The results showed that the extract significantly ameliorates depressive-like behaviors in chronic restraint stress mice.…”
Section: Dosementioning
confidence: 99%
“…Currently, a large number of in vivo studies suggest that nutraceuticals (including prebiotics, probiotics, and synbiotics) are used to maintain the normal gut biota and to prevent or treat GIT-related diseases [117,118,130,131,132,133,134,135,136,137,138]. The GIT contains a complex polymicrobial community that consists of bacteria, viruses, archaea, fungi, and parasites [99,139,140,141].…”
Section: Effects On Gut Microbiota and Enterocytesmentioning
confidence: 99%